Enhancing mathematical concept understanding: The influence of scaffolding in team-assisted individualization based on self-regulation - Pakpahan, Nicolaus; Kamid, Kamid; Muhammad, Damris (Indonesian Journal of Science and Mathematics Education, 2025)
Effective learning requires strategies that support students' understanding of mathematical concepts and promote independent learning. This study examines the impact of scaffolding in Team Assisted Individualization (TAI) on students' mathematical conceptual understanding and the role of self-regulation in the learning process. The research employs a quasi-experimental design with a nonequivalent pre-test and post-test control group design involving 109 randomly selected high school students. Data analysis was conducted to compare the effectiveness of TAI with scaffolding, TAI without scaffolding, and Direct Instruction, as well as to evaluate the interaction between learning models and students' self-regulation levels. The results indicate that TAI with scaffolding significantly enhances students' mathematical conceptual understanding compared to other methods. Furthermore, students with high self-regulation demonstrated better conceptual understanding. Interaction analysis reveals that students with moderate to high self-regulation benefit more from scaffolding-based learning. The study concludes that scaffolding in TAI improves students' mathematical conceptual understanding. These findings highlight the importance of gradual scaffolding in supporting students' comprehension before they transition to independent learning. Additionally, this model effectively enhances students' autonomy and critical thinking skills in the classroom.